Mechanical, Chemical, And Morphological Characterization Of 1% Nanofiber-Reinforced Self-Cure Acrylic For Denture Applications - Ira Artilia; Gina Adry Syahira; Zwista Yulia Dewi; Asih Rahaju; Rheni Safira Dewi; Nunung Nuraeni; Nurrahmi Handayani; Atia Nurul Sidiqa (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Self-curing resin acrylic (SC-AR) is widely used for biomedical appliances, particularly prostheses, due to its rapid manipulation and suitability for single-visit fabrication. However, its relatively low mechanical strength may increase fracture susceptibility. This study evaluated the effect of incorporating 1 wt% polyacrylonitrile polymethyl methacrylate electrospinning nanofibers (e-nanoPAN-PMMA) on the physicochemical, mechanical, and morphological characteristics of SC-AR. Materials and Methods: SC-AR specimens were divided into conventional SC-AR (SC-ARc) and nano-reinforced SC-AR (SC-ARnano) groups. Chemical characteristics were evaluated using X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). Flexural strength (FS) and flexural modulus (FM) were assessed using a three-point bending test, while fracture-surface morphology was examined using scanning electron microscopy (SEM). Data were analyzed using an independent t-test (P≤0.05). Results and Discussion: SC-ARnano exhibited significantly higher FS and FM than SC-ARc (P≤0.05). XRD patterns showed characteristic polymeric resin features in both groups, with no additional crystalline peaks in SC-ARnano. FTIR revealed a nitrile absorption band in SC-ARnano. SEM demonstrated nanofibers embedded within the resin matrix, with no detectable surface porosity. Conclusion: Incorporation of 1 wt% e-nanoPAN-PMMA significantly improved the mechanical properties of SC-AR while maintaining its physicochemical characteristics. SC-ARnano demonstrates potential as a reinforced acrylic resin for biomedical applications.